Social Relationships and Risk of Type 2 Diabetes Among Postmenopausal Women. (26th April 2019) - Hendryx, Michael; Nicholson, Wanda; Manson, JoAnn E; Kroenke, Candyce H; Lee, Jennifer; Weitlauf, Julie C; Garcia, Lorena; Jonasson, Junmei M; Wactawski-Wende, Jean; Luo, Juhua
Abstract: Objectives: We examined whether social relationship variables (social support, social strain, social network size, and stressful life events) were associated with risk of developing type 2 diabetes among postmenopausal women. Method: 139, 924 postmenopausal women aged 50–79 years without prevalent diabetes at baseline were followed for a mean of 14 years. 19, 240 women developed diabetes. Multivariable Cox proportional hazard models tested associations between social relationship variables and diabetes incidence after consideration of demographics, depressive symptoms, and lifestyle behaviors. We also examined moderating effects of obesity and race/ethnicity, and we tested whether social variable associations were mediated by lifestyle or depressive symptoms. Results: Compared with the lowest quartile, women in the highest social support quartile had lower risk of diabetes after adjusting for demographic factors, health behaviors, and depressive symptoms (hazard ratio [HR] = 0.93, 95% confidence interval [CI] = 0.89–0.97). Social strain (HR = 1.09, 95% CI = 1.04–1.13) and stressful life events (HR = 1.10, 95% CI = 1.05–1.15) were associated with higher diabetes risks. The association between diabetes and social strain was stronger among African American women. Social relationship variables had direct relationships to diabetes, as well as indirect effects partially mediated by lifestyle and depressive symptoms. Discussion: Social support, social strain, and stressful life events were associated with diabetes risk among postmenopausal women independently of demographic factors and health behaviors. In addition to healthy behaviors such as diet and physical activity, healthy social relationships among older women may be important in the prevention of diabetes.